Complications of Implanted Nonbiologic Devices—An Overview - Kwaan, Hau C. (Seminars in Thrombosis and Hemostasis, 2018)
Under physiologic conditions, blood is contained within the vascular space lined with smooth endothelial cells. When various devices made of nonbiologic material are implanted, blood will be exposed to a foreign surface. A series of events ensue and may lead to many complications, including thrombosis, hemolysis, thrombocytopenia, bleeding, infection, and malfunction of the device. The incidence, manifestations, and special characteristics of these complications vary with different types of implanted devices. However, they have in common an important pathogenic pathway that of an exposure to a foreign surface. Despite the development of improved versions of these devices, more research on the causative factors of these complications is needed to take preventive and corrective measures, particularly those that enhance the process of healing by re-endothelialization of the foreign surface. This article is a brief review of the complications encountered in blood-contacting devices.
Keywords: biomaterial; implanted devices; thrombosis; endothelial cells; thrombocytopenia